Tanggung Jawab Hukum Tenaga Kesehatan Dalam Kasus Malpraktek Medik di Rumah Sakit - Irpan Suriadiata; Anggi Purnama Tradesa; Angga Dinata (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
This study aims to analyze the legal responsibility of health workers in cases of medical malpractice in hospitals according to Indonesian laws and regulations. It also examines the construction of legal responsibility of health workers in cases of medical malpractice from the perspective of civil, criminal, and administrative law. It also examines the legal responsibility of hospitals for medical malpractice committed by health workers within the framework of employment relationships and the provision of health services. This study uses a normative legal method, which views law as written norms in laws and regulations and legally binding behavioral guidelines. The research approach includes a statutory approach and a conceptual approach. Primary, secondary, and tertiary legal materials are processed through inventory, classification, and systematics to facilitate analysis. The analysis is conducted by applying grammatical, systematic, and teleological legal interpretations, and using legal theory and principles as analytical tools to assess the forms and mechanisms of legal protection. The research findings indicate that the legal system needs to reconstruct its accountability framework by clarifying the boundaries between medical risk and malpractice, and assigning civil, criminal, and administrative responsibilities proportionally. Hospitals should strengthen their institutional accountability through the application of the principles of vicarious liability and corporate liability, ensuring effective oversight, procedures, and risk management. Preventive approaches, health law education for medical personnel, and non-litigation dispute resolution mechanisms can improve patient safety